2012
DOI: 10.5194/angeo-30-1055-2012
|View full text |Cite
|
Sign up to set email alerts
|

Temperature thresholds for chlorine activation and ozone loss in the polar stratosphere

Abstract: Abstract. Low stratospheric temperatures are known to be responsible for heterogeneous chlorine activation that leads to polar ozone depletion. Here, we discuss the temperature threshold below which substantial chlorine activation occurs. We suggest that the onset of chlorine activation is dominated by reactions on cold binary aerosol particles, without the formation of polar stratospheric clouds (PSCs), i.e. without any significant uptake of HNO 3 from the gas phase. Using reaction rates on cold binary aeroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(131 citation statements)
references
References 131 publications
7
124
0
Order By: Relevance
“…Nonetheless, they represent the first long-term, vortex-wide 15 observational-based record of SAD and VD and can be used to compare CALIOP stratospheric data with in situ particle measurements and to test parameterizations of the chemical and radiative effects of particles in current and future theoretical models. Since the SAD and VD estimates cover the full range of CALIOP data, including "sub-visible" PSCs as well as background aerosols, they may prove especially valuable in studies of the role of PSCs relative to that of cold background aerosols in early-season chlorine activation (e.g., Wegner et al, 2016;Drdla and Müller, 2012). 20…”
Section: Particle Surface Area Density and Volume Densitymentioning
confidence: 99%
“…Nonetheless, they represent the first long-term, vortex-wide 15 observational-based record of SAD and VD and can be used to compare CALIOP stratospheric data with in situ particle measurements and to test parameterizations of the chemical and radiative effects of particles in current and future theoretical models. Since the SAD and VD estimates cover the full range of CALIOP data, including "sub-visible" PSCs as well as background aerosols, they may prove especially valuable in studies of the role of PSCs relative to that of cold background aerosols in early-season chlorine activation (e.g., Wegner et al, 2016;Drdla and Müller, 2012). 20…”
Section: Particle Surface Area Density and Volume Densitymentioning
confidence: 99%
“…The relative roles and temperature dependencies of surface reactions on and in water ice, nitric acid trihydrate ice, and supercooled liquid sulfuric acid−water−nitric acid and binary sulfuric acid−water particles at background levels have been research topics since the late 1980s, and some important questions have recently reemerged. Some recent studies have suggested that heterogeneous chemistry taking place on background particles of sulfuric acid and water is sufficient to explain nearly all of the chlorine activation (17)(18)(19) and ozone losses in both the Arctic and Antarctic (17) without any need for temperatures below −78°C or formation of polar stratospheric clouds, which would represent a major change in understanding. The potential for liquid binary aerosols to play some role in ozone loss under cold conditions was first identified decades ago (20,21).…”
Section: Lower Stratospheric Chemistrymentioning
confidence: 99%
“…In addition to PSCs, chlorine activation can also occur on cold sulfate aerosols (e.g. Hanson et al, 1994;Drdla and Müller, 2012;Wegner et al, 2012;Solomon et al, 2015). In contrast, a warmer, more disturbed polar vortex should be accompanied by much smaller chemical destruction of ozone and enhanced transport from lower latitudes.…”
Section: Introductionmentioning
confidence: 99%